Femtocell E2E performance analysis and stability in the UMTS network / Mohamad Safwan Othman - Othman, Mohamad Safwan (2014)
The femtocells cover a small area same as Wi-Fi where they are competing with each other. The femto unit, low-cost type of cellular base stations, where optimized for home used and enterprise (small business). The purpose of this paper is to study the femto implemantion and analyze the End-to-end (E2E) performance of the femto. We are focusing on the End-to-end (E2E) femto analysis, the performance is measured based on the best parameter sets in femto with the acceptable value in the real networks. The circuit switch (CS) and packet switch (PS) perfonnance is talking part to determine the best quality performance of the femto. The deployment of the femtocell in the network can improve the network quality, support coverage especially in the building area and reduce the budget of implementing the macrocell.